Strategi Penjualan Dalam Meningkatkan Volume Penjualan Pelaku Usaha Ayam Geprek Batanghari Lampung Timur - Ima Mega Septiana Putri; Tarisa Varagita; Carmidah Carmidah (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
This study aims to determine the sales strategy in increasing sales volume at the Ayam Geprek 7000s food stall, Batanghari sub-district. The type of research used is qualitative research using SWOT analysis techniques. The results of this study show the strengths of the 7000s geprek chicken food stalls, namely quality product quality, strategic location, quality human resources, and a menu that many people are interested in. While the weaknesses are not implementing optimal strategies and not using technology. Opportunities at the 7000 geprek chicken food stalls are a lot of market share. Then the threat faced is that there are many competitors, so